Фибулы византийского круга в Восточной Европе (литые дунайско-иллирийские) - Гавритухин, И.О. (Материалы по археологии, истории и этнографии Таврии, 2002)
In this article we examine fibulas consisting of two parts with an arbalest-shaped spring with low taut rope tied up or imitating a garter, and, what is more characteristic, a receiver, put far from the stem. In profile it gives a “U-shape” form.